Neoadjuvant Chemotherapy Use for Nonmetastatic Breast Cancer at Five Public South African Hospitals and Impact on Time to Initial Cancer Therapy. (5th December 2018) - O'Neil, Daniel S.; Nietz, Sarah; Buccimazza, Ines; Singh, Urishka; Čačala, Sharon; Stopforth, Laura W.; Joffe, Maureen; Jacobson, Judith S.; Neugut, Alfred I.; Crew, Katherine D.; Ruff, Paul; Cubasch, Herbert
Abstract: Background: In the U.S., neoadjuvant chemotherapy (NAC) for nonmetastatic breast cancer (BC) is used with extensive disease and aggressive molecular subtypes. Little is known about the influence of demographic characteristics, clinical factors, and resource constraints on NAC use in Africa. Materials and Methods: We studied NAC use in a cohort of women with stage I–III BC enrolled in the South African Breast Cancer and HIV Outcomes study at five hospitals. We analyzed associations between NAC receipt and sociodemographic and clinical factors, and we developed Cox regression models for predictors of time to first treatment with NAC versus surgery. Results: Of 810 patients, 505 (62.3%) received NAC. Multivariate analysis found associations between NAC use and black race (odds ratio [OR] 0.49; 95% confidence limit [CI], 0.25–0.96), younger age (OR 0.95; 95% CI, 0.92–0.97 for each year), T‐stage (T4 versus T1: OR 136.29; 95% CI, 41.80–444.44), N‐stage (N2 versus N0: OR 35.64; 95% CI, 16.56–76.73), and subtype (triple‐negative versus luminal A: OR 5.16; 95% CI, 1.88–14.12). Sites differed in NAC use (Site D versus Site A: OR 5.73; 95% CI, 2.72–12.08; Site B versus Site A: OR 0.37; 95% CI, 0.16–0.86) and time to first treatment: Site A, 50 days to NAC versus 30 days to primary surgery (hazard ratio [HR] 1.84; 95% CI, 1.25–2.71); Site D, 101 days to NAC versus 126 days to primary surgery (HR 0.49; 95% CI, 0.27–0.89). Conclusion: NAC use for BC at these South African hospitals was associated with both tumor characteristics and heterogenous resource constraints. Abstract : In sub‐Saharan Africa, clinical decisions can be affected by resource constraints. This article analyzes the clinical and sociodemographic factors associated with receiving neoadjuvant chemotherapy among patients from a previously existing cohort: women enrolled in the prospective South African Breast Cancer and HIV Outcomes study.